2024
DOI: 10.1111/jcap.12447
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and lifestyle behavior changes during COVID‐19 among families living in poverty: A descriptive phenomenological study

Nagwan R. Zahry,
Jiying Ling,
Lorraine B. Robbins

Abstract: ProblemFamilies living in poverty may be particularly vulnerable to the deleterious effects of the coronavirus disease (COVID‐19). The current study focuses on caregivers of preschoolers aged 3–5 years old who lived in poverty to explore how COVID‐19 affected mental health and lifestyle behaviors and what coping strategies were helpful for dealing with challenges induced by COVID‐19.MethodsA qualitative study was conducted using individual semi‐structured interviews with 17 caregivers.FindingsBoth caregivers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A number of studies showed that parental financial stress due to the COVID-19 lockdown related to parental mental health, which was finally significantly associated with child and adolescent psychological well-being [48,49]. Low socioeconomic status signifies more vulnerability in several aspects, as it means less opportunity to access adaptive resources, such as safe outdoor activities and healthy food, and also less access to the healthcare system [50][51][52]. It should be noted that the disease outbreak made inequality more evident in many countries, including Thailand [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies showed that parental financial stress due to the COVID-19 lockdown related to parental mental health, which was finally significantly associated with child and adolescent psychological well-being [48,49]. Low socioeconomic status signifies more vulnerability in several aspects, as it means less opportunity to access adaptive resources, such as safe outdoor activities and healthy food, and also less access to the healthcare system [50][51][52]. It should be noted that the disease outbreak made inequality more evident in many countries, including Thailand [53,54].…”
Section: Discussionmentioning
confidence: 99%